(untitled) (Journal of the College of Basic Education, 2024)
The current research aims to identify (building a proposed program according to logical thinking skills in Arabic grammar), and to achieve the goal of the research, the researcher followed the descriptive approach; Being the appropriate approach for the research objective, the researcher prepared the proposed program according to logical thinking skills, and included the steps involved in building the program, which is the planning stage (analysis and design), reviewing previous studies, and identifying the starting points of the program. Determining the foundations on which the program is based, and the components of the program are defining the objectives of the program, challenging the content of the program, defining the input behavior of the program, defining the methods and strategies, defining the activities for the program, defining the teaching aids, evaluation, and feedback. And organizing the content of the program (the teacher’s guide and the student’s guide), and the stage of the validity of the program.